Neurophilosophy of free will : from libertarian illusions to a concept of natural autonomy - Walter, Henrik (MIT Press, 2001)
Walter's answer to whether there is free will is, It depends. The basic questions concerning free will are (1) whether we are able to choose other than we actually do, (2) whether our choices are made intelligibly, and (3) whether we are really the originators of our choices. According to Walter, freedom of will is an illusion if we mean by it that under identical conditions we would be able to do or decide otherwise, while simultaneously acting only for reasons and being the true originators of our actions. In place of this scientifically untenable strong version of free will, Walter offers what he calls natural autonomy--self-determination unaided by supernatural powers that could exist even in an entirely determined universe. Although natural autonomy can support neither our traditional concept of guilt nor certain cherished illusions about ourselves, it does not imply the abandonment of all concepts of responsibility. For we are not mere marionettes, with no influence over our thoughts or actions.